The Role of Livestock in Rural Households in Nepal - Jha, Dilip Kumar (International Journal of Publication and Social Studies, 2019)
This paper investigates the livestock asset positions of rural households and the contribution of livestock to their income in Nepal. The research is conducted in household of the rural areas in plain (Terai) region. The primary data is collected on the om snow ball concept and secondary data to support the research. The findings of the research shows the different perspectives of the rearing the livestock in in different households regardless of the households economy. The majority of rural households keep livestock; the rural poor, defined as those living in rural areas and belonging to the bottom expenditure quintile, are more likely to keep livestock than those in higher quintiles. Rural poor household who keeps livestock for income generating purposes whereas a bit well-off as a consuming and income enhancing purposes. There are minor differences in herd composition between households economy. Small ruminant is common in the poor economy of the rural household whereas well off households goes for both on their choice of increasing the income as well consumption. Regardless of household economy, most of the households would like to rear the livestock for their emergency funding or additional income.